Early injury evaluation following concussion is associated with improved recovery time in children and adolescents. Issue 12 (December 2021) - Cassimatis, Maree; Orr, Rhonda; Fyffe, Andrew; Browne, Gary
Abstract: Objectives: Delayed treatment for paediatric concussion may impact recovery trajectory. This study aims to determine the relationship between time to evaluation and concussion recovery in children and adolescents. Design: Retrospective cross-sectional study. Methods: Records from 341 children and adolescents, aged 7–18 years, from a tertiary referral concussion clinic were analysed. All participants were assessed using a standardised concussion test battery by a specialist concussion physician and graded exercise testing. Evaluation time was defined as the number of days from injury occurrence to first presentation at the concussion clinic. Three distinct time to evaluation periods were categorised as: early evaluation (<14 days), mid evaluation (14–28 days), and late evaluation (>28 days). The main outcome measure was recovery time (days). Results: A total of 341 participants (mean age 13.0 ± 2.3, 74% male) were included in the study. Of these, 89 received evaluation during the early phase (mean age 12.2 ± 2.5, 65% male), 124 during the mid phase (mean age 13.1 ± 2.2, 81% male) and 128 during the late phase (mean age 13.5 ± 2.1, 75% male) following injury. Participants receiving late evaluation took three times longer to recover (mean 148.0 days, 95% CI: 121.1–173.9) compared to early (mean 38.7 days, 95% CI: 30.7–46.7) and mid (mean 51.5 days, 95% CI: 39.7–63.4) evaluation. There was a strong positive correlation between recovery time and evaluation time ( r  = 0.66, p  < 0.001). Conclusions: Delaying time to evaluation following a concussion can significantly prolong recovery from injury in children and adolescents.